Effect of nutrients and plant-population density on yield and quality of round gourd (Citrullus lanatus var fistulosus) - KANWAR, J S; KHURANA, D S; SINGH, BIKRAMJIT (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1987-88 to study the effect of nutrients and plant density on yield and quality afround gourd [Citrullus lanatus (Thunb.) Mansf. & Nakai var fistulosus (Stocks) Mansf.]. The experiment was laid out in split-plot design having different plant spacings (22.5,30.0 and 45.0 cm between plants) in main plot, and various combinations af nitrogen (75. 100 and 125 kg/hal and phosphorus (50. 62.5 and 75 kg/hal in subplot. The plant spacing of 90 cm X 22.5 cm gave rne maximum fruit yield (10.9 tonnes/ha). Application of N and P had positive correlation with quality attributes ie total soluble solids. ascorbic acid and mineral matter. during both the years. Nand P @ 100 and 75 kg/ha gave maximum fruit. yield of 10.2 and 9.9 tonnes/ha respectively.